2013
DOI: 10.1007/s10548-013-0320-z
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex Activated Bilaterally by a Tilt Board Balance Task: A Functional Near-Infrared Spectroscopy Study in a Semi-Immersive Virtual Reality Environment

Abstract: The aim of this study was to assess the prefrontal cortex (PFC) oxygenation response to a 5-min incremental tilt board balance task (ITBBT) in a semi-immersive virtual reality (VR) environment driven by a depth-sensing camera. It was hypothesized that the PFC would be bilaterally activated in response to the increase of the ITBBT difficulty, given the PFC involvement in the allocation of the attentional resources to maintain postural control. Twenty-two healthy male subjects were asked to use medial-lateral po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…The velcro fastener was positioned between the flexible probe holders and the black cloth. Although the subsystolic pressure induced by the velcro fastener was not adequate to induce a transient complete blockage of the skin circulation as in Takahashi's study (Takahashi et al, 2011), the pressure on the optodes was considered adequate to induce a consistent reduction of skin blood flow, if signals corresponding to the shape and size of the optodes were evident on the head skin for at least 15 minutes after the experimental section Ferrari et al, 2014). We interpreted the presence on the skin of depressed cutaneous areas as prove that the applied subsystolic pressure was able to squeeze part of the venous blood volume out of the forehead skin.…”
Section: Functional Near-infrared Spectroscopymentioning
confidence: 92%
“…The velcro fastener was positioned between the flexible probe holders and the black cloth. Although the subsystolic pressure induced by the velcro fastener was not adequate to induce a transient complete blockage of the skin circulation as in Takahashi's study (Takahashi et al, 2011), the pressure on the optodes was considered adequate to induce a consistent reduction of skin blood flow, if signals corresponding to the shape and size of the optodes were evident on the head skin for at least 15 minutes after the experimental section Ferrari et al, 2014). We interpreted the presence on the skin of depressed cutaneous areas as prove that the applied subsystolic pressure was able to squeeze part of the venous blood volume out of the forehead skin.…”
Section: Functional Near-infrared Spectroscopymentioning
confidence: 92%
“…The prefrontal involvement in the active balance tasks was confirmed using a virtual tilt board task, which showed a positive correlation between task difficulty and prefrontal activation. 44 In addition, Mahoney et al 45 reported a larger prefrontal activation during a dual-task standing task in patients with Parkinson's disease compared with healthy subjects or patients with mild Parkinsonian signs. These findings also supported the notion that the PFC may compensate for the impaired postural ability in patients with neurological disorders.…”
Section: Neural Mechanism For Postural Controlmentioning
confidence: 99%
“…Most previous studies examining postural control have employed indirect methods such as mental imagery of standing (Zwergal et al, 2012; Malouin et al, 2003; Jahn et al, 2004), virtual reality (Basso Moro et al, 2014; Ferrari et al, 2014) or even simulated active balance during supine position (Karim et al, 2014) instead of measuring activity online during actual standing. Findings from these studies employing indirect methods to assess cortical postural control suggest that the prefrontal cortex plays a critical role in healthy younger adults (Basso Moro et al, 2014; Ferrari et al, 2014) and in patients with neurological conditions like stroke (Fujimoto et al, 2014). However, in order to better understand the mechanism of postural instability in healthy older adults and in patients with PS, direct online cortical measurement in the prefrontal regions during upright standing is needed.…”
Section: Introductionmentioning
confidence: 99%